The Role of Intolerance of Uncertainty in Social Anxiety Subtypes. Issue 3 (10th July 2013) - Whiting, Sara E.; Jenkins, Whitney S.; May, Anna C.; Rudy, Brittany M.; Davis, Thompson E.; Reuther, Erin T.
<x xml:space="preserve">Abstract</x> Objectives Intolerance of uncertainty (IU) is thought to underlie several internalizing disorders; however, it has only begun to be explored within social anxiety (SA). This study extends previous findings by examining IU's relation to performance and interaction SA subtypes and by accounting for obsessive‐compulsive symptoms. Methods A total of 472 undergraduates completed measures of IU, SA, perfectionism, worry, obsessions/compulsions, and fear of negative evaluation (FNE). Results IU and obsessions/compulsions predicted performance SA beyond FNE. IU predicted interaction SA beyond FNE. Inhibitory anxiety IU contributed to both SA types but contributed more to performance SA. Prospective anxiety IU was negatively related to performance SA and unrelated to interaction SA, though a trend emerged. Contrasts between those high in one SA type, both, or neither revealed IU was highest when both types were present. Conclusions Inhibitory IU plays a significant role in both SA subtypes and may play a slightly greater role in performance SA.